Sexual Orientation and Adolescent Time Use: How Sexual Minority Youth Spend Their Time. Issue 3 (7th May 2019) - Perales, Francisco; Campbell, Alice; O'Flaherty, Martin
Abstract : This study combines minority stress and ecological perspectives to theorize the associations between adolescents' sexual orientation and time use. Hypotheses are tested using data from a national sample of Australian adolescents aged 14–15 years ( Longitudinal Study of Australian Children ; n  =   3, 060). Compared to heterosexual adolescents, sexual minority adolescents spent less time with their siblings and fathers, more time alone, less time in active leisure‐ and school‐based activities, and more time in nonactive leisure. There were no differences between sexual minority and heterosexual adolescents in time spent with mothers, peers, and in screen‐based leisure. Some associations were gendered. Collectively, the results suggest that sexual minority adolescents may withdraw or be excluded from critical developmental activities and the company of key social partners.